The future of the past: why classical studies still matter : Athenian Dialogues IV - Giannakēs, Geōrgios K.; Papangelēs, Theodōros D.; Renkakos, Antōnios (Trends in classics, 2024)
This collective volume contains 27 original studies that address in a critical way the position of classical studies in the twenty-first century and its challenges, as captured in the oxymoron of the theme title ‘the future of the past’. The relevance of classical antiquity is reflected in all aspects of modern life: the sciences, the linguistic forms, literary expressions, cultural tradition, religion and ethics, philosophical thinking, modes of argument, political theory, history, the arts, and an entire host of other areas—in a word, much of what modern man is. As the conversation between past and present is best demonstrated at the intersection of different disciplines and cultural trends, interdisciplinary and intercultural topics are discussed in the essays. The contributions are organized in thematic groups according to the topics and sub-topics covered, and explore new ways of viewing the values of the classical past and their relevance to the present and future of societies. The work is of special relevance to scholars interested in classical studies, ancient history, critical thinking, the reception of classical ideas in the modern world, and the relation of the past with the present and the future of humanity
Keywords: Konferenzschrift; Altsprachlicher Unterricht; Klassische Philologie